2018
DOI: 10.21873/anticanres.12560
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Image-guided targeted Biopsies to Radical Prostatectomy Specimens for Accurate Characterization of the Index Tumor in Prostate Cancer

Abstract: TBx has a high sensitivity for characterization of index lesions, with a good concordance for topographic and Gleason grading accuracy between biopsy and surgical specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Francesco et al reported it as 82.2% (n = 152) [5,33]. In this study, which used bpMRI-TRUS fusion biopsy, the accuracy of IT assessment was 85.5% (59/69), which we considered to be comparable to previous mpMRI reports.…”
Section: Discussionsupporting
confidence: 80%
“…Francesco et al reported it as 82.2% (n = 152) [5,33]. In this study, which used bpMRI-TRUS fusion biopsy, the accuracy of IT assessment was 85.5% (59/69), which we considered to be comparable to previous mpMRI reports.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, if an index tumor in the central zone is suggested during preoperative evaluation, a multimodal treatment combining neoadjuvant hormonal therapy and/or chemotherapy with radical prostatectomy may be required. Recently, index tumors have been evaluated preoperatively using radiological and biopsy approach [ 24 , 25 ]. Our results may allow urologists and patients to reconsider the therapeutic strategies for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%